2002
DOI: 10.1177/0305735602302005
|View full text |Cite
|
Sign up to set email alerts
|

Social and Musical Co-Ordination between Members of a String Quartet: An Exploratory Study

Abstract: This paper examines the social and musical co-ordination between members of a student string quartet in rehearsal and performance. Devised as an exploratory observation and interview study, a two-tier analysis of the data is undertaken. The first deals with broadly socio-cultural issues, the second with moment-by-moment social and musical co-ordination. The results indicate that there are many factors that influence the functioning of such an ensemble. These include personal concerns about particular social dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
156
0
16

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(181 citation statements)
references
References 13 publications
9
156
0
16
Order By: Relevance
“…Besides performance issues, where the leadership of the first violin emerged, cohesion in the group depended also on merely organizational issues: the first violin was the leader in administrative issues too and the second violin was responsible for offering social support to the group. Davidson & Good [43] analysed social and musical coordination between members of a student string quartet in rehearsal and performance conditions. They found that social and musical coordination depends on many factors, including both socio-emotional issues (e.g.…”
Section: Social Interaction In Small Ensemblesmentioning
confidence: 99%
“…Besides performance issues, where the leadership of the first violin emerged, cohesion in the group depended also on merely organizational issues: the first violin was the leader in administrative issues too and the second violin was responsible for offering social support to the group. Davidson & Good [43] analysed social and musical coordination between members of a student string quartet in rehearsal and performance conditions. They found that social and musical coordination depends on many factors, including both socio-emotional issues (e.g.…”
Section: Social Interaction In Small Ensemblesmentioning
confidence: 99%
“…During improvisation sections a distinction may be drawn between the interplay of 'stocks of musical knowledge' and truly 'spontaneous musical utterances' (Davidson & Good, 2002). For example, musicians describe how they listen to recordings they have made and hear themselves playing phrases they have never previously practised but which have emerged as a result of what the other musicians were playing at the time.…”
Section: E M P a T H E T I C C R E A T I V I T Ymentioning
confidence: 99%
“…A further hierarchical distinction was made between sympathetic and empathetic levels of attunement between the participants (Arnold, 1998(Arnold, , 2003(Arnold, , 2004Seddon, in press). Evaluation of the improvisations produced was based upon researcher judgements of the production of 'spontaneous musical utterances' as distinct from the 'exchange of stocks of musical knowledge' (Davidson & Good, 2002), along with support from participant judgements of the same improvisations.…”
Section: R E S E a R C H C O N T E X T A N D M E T H O D Smentioning
confidence: 99%
“…Music performance, and more precisely ensemble performance, become a fruitful field of research (Davidson & Good 2002;Ginsborg & King, 2007;Goodman, 2002;Williamon & Davidson, 2002). In this respect, musicians'perceptive and attentional skills and their neurophysiological implications are the main topic of several studies (Altenmüller, Wiedendanger & Kesselring, 2006;Alonso et al 2008;Schlaug, 2001).…”
Section: Introductionmentioning
confidence: 99%